Nicolas Poussin friendship and the love of painting - Cropper, Elizabeth 1944-; Dempsey, Charles 1937- (Princeton Univ. Press, 1996)
By investigating the important figures who were close to the painter Nicolas Poussin (1594-1665), Elizabeth Cropper and Charles Dempsey allow the reader to enter not only the Rome where he lived but also the Rome of antiquity, which he admired and tried to reconstruct. The authors argue that Poussin's works were structured by his friendships, as well as by his study of ancient history and early Christian archaeology, his exploration of the poetry and mystery of ancient places, and his conception of his paintings as gifts rather than commercial objects. By looking into this rich background, they also show how Poussin introduced into his theory and practice of painting a new concept of the inherent expressiveness of form that was quite different from the then prevailing conventions for depicting the passions and affections.
Keywords: Poussin, Nicolas <1594?-1665> - Amis et relations; Poussin, Nicolas <1594?-1665> - Critique et interprétation; Poussin, Nicolas, 1594?-1665 -- Criticism and interpretation; Poussin, Nicolas, 1594?-1665 -- Friends and associates; Dal Pozzo, Cassiano -- 1588-1657; Poussin, Nicolas -- 1594-1665; Montaigne, Michel Eyquem de -- 1533-1592; Giustiniani, Vincenzo -- 1564-1637; Beïnvloeding; Schilderijen; Malerei; Freundeskreis